2009
DOI: 10.1186/1471-2202-10-28
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of Y-box binding protein 1 in brain tissue of rats, macaques, and humans

Abstract: BackgroundThe Y-box binding protein 1 (YB-1) is considered to be one of the key regulators of transcription and translation. However, so far only limited knowledge exists regarding its cellular distribution in the adult brain.ResultsAnalysis of YB-1 immunolabelling as well as double-labelling with the neuronal marker NeuN in rat brain tissue revealed a predominant neuronal expression in the dentate gyrus, the cornu ammonis pyramidal cell layer, layer III of the piriform cortex as well as throughout all layers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The signal of the immunoperoxidase-treated sections was captured with the computer-assisted imaging system StereoInvestigator 6.0 (Microbrightfield Europe, Magdeburg, Germany) as described previously (Unkruer et al, 2009). The hardware consists of a Leica DMLB microscope (Leica, Bensheim, Germany), a Plan-Neofluar lens (Leica, Bensheim, Germany), a single chip charge coupled device (CCD) color camera (CX9000, Microbrightfield Europe, Magdeburg, Germany), and an AMD Athlon 64 Processor.…”
Section: Immunohistological Evaluationmentioning
confidence: 99%
“…The signal of the immunoperoxidase-treated sections was captured with the computer-assisted imaging system StereoInvestigator 6.0 (Microbrightfield Europe, Magdeburg, Germany) as described previously (Unkruer et al, 2009). The hardware consists of a Leica DMLB microscope (Leica, Bensheim, Germany), a Plan-Neofluar lens (Leica, Bensheim, Germany), a single chip charge coupled device (CCD) color camera (CX9000, Microbrightfield Europe, Magdeburg, Germany), and an AMD Athlon 64 Processor.…”
Section: Immunohistological Evaluationmentioning
confidence: 99%
“…The immunoreaction was visualized using a corresponding biotin-labeled secondary antiserum and the nickel-intensified diaminobenzidine reaction. Cell counting was done using the computerassisted imaging system, StereoInvestigator 6.0 (Microbrightfield Europe, Magdeburg, Germany), as described recently [16]. Newborn neurons were identified by double labeling of BrdU and NeuN and analyzed using a confocal microscope (Zeiss LSM 410 microscope, Zeiss, Oberkochen, Germany) as described earlier [13,14].…”
Section: Methodsmentioning
confidence: 99%
“…Neurons show a predomi-nant YB-1 expression adult rat, macaque and human brains. YB-1 has been found to be imperative for the maintenance of mouse neuronal stem cells (Unkrüer et al, 2009). Fotovati et al, (2011 found a high expression of YB-1 in subventricular zone of normal E14 mouse tissues.…”
Section: Yb-1 and Brain Cancermentioning
confidence: 99%
“…In rat brain, the YB-1 is found to be highly expressed in the dentate gyrus, cornuammonis pyramidal cell layer and layer III of the piriformcortex. Neuronal YB-1 expression in explicit brain areas ranges to the adult brain and amounts relevant altitudes in the adult rat, macaque and human brain (Unkrüer et al, 2009). However, a decline in the YB-1 brain expression in the postnatal phase has been described (Funakoshi et al, 2003).…”
Section: Yb-1 and Brain Cancermentioning
confidence: 99%
See 1 more Smart Citation